A Green and Efficient Method for the Preparation of 3,4-Dihydropyrimidin-2(1H)-ones Using Quaternary Ammonium-Treated Clay in Water - Soheil Sayyahi; Sedigheh Jahanbakhshi; Zahra Dehghani (Journal of Chemistry)
A variety of 3,4-dihydropyrimidin-2(1H)-ones derivatives were synthesized via three-component Biginelli reaction. The quaternary ammonium-treated clay-catalyzed process proved to be simple, efficient, and environmentally friendly.